The ABCs of the anterior cruciate ligament: a primer for magnetic resonance imaging assessment of the normal, injured and surgically repaired anterior cruciate ligament. Issue 11 (28th October 2009) - Bining, J; Andrews, G; Forster, B B
Abstract : This article reviews the magnetic resonance imaging (MRI) findings of the native and reconstructed anterior cruciate ligament (ACL). MRI is the most accurate non-invasive modality to evaluate the ACL. Tears of the ACL manifest with direct and indirect signs. The reconstructed ACL has several complications including re-tear and anterior arthrofibrosis, which are also accurately assessed using MRI.